2015
DOI: 10.3938/jkps.67.7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment plan comparison of linac step and shoot, tomotherapy, rapidarc, and proton therapy for prostate cancer by using the dosimetrical and the biological indices

Abstract: The purpose of this study was to use various dosimetrical indices to determine the best IMRT modality technique for treating patients with prostate cancer. Ten patients with prostate cancer were included in this study. Intensity modulated radiation therapy plans were designed to include different modalities, including the linac step and shoot, Tomotherapy, RapidArc, and Proton systems. Various dosimetrical indices, like the prescription isodose to target volume (PITV) ratio, conformity index (CI), homogeneity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A dosimetric Korean study compared both modalities used in our study as well as Tomotherapy and Proton. Authors concluded that better PTV coverage and superior rectal and bowel sparing in high dose volumes were attained with VMAT compared to other modalities albeit all of them achieved the desired constraints (Lee et al, 2015). Nevertheless, no dosimetric advantage was reported in this work.…”
Section: Discussionmentioning
confidence: 68%
“…A dosimetric Korean study compared both modalities used in our study as well as Tomotherapy and Proton. Authors concluded that better PTV coverage and superior rectal and bowel sparing in high dose volumes were attained with VMAT compared to other modalities albeit all of them achieved the desired constraints (Lee et al, 2015). Nevertheless, no dosimetric advantage was reported in this work.…”
Section: Discussionmentioning
confidence: 68%
“…Lee et al performed a planning study on ten patients with prostate cancer 29 . Different modalities of IMRT were used, like the linac step and shoot, RapidArc and proton systems.…”
Section: Discussionmentioning
confidence: 99%